Removal of organic dyes from textile wastewater using green synthesized metal oxide heterostructures decorated carbon-based nanomaterials - Bopape, Dineo Anna (My University, 2023)
Despite the persistent problem of water scarcity, water resource contamination is on the rise because of the growing trend of urbanisation and industrialization. Contaminants, such as dyes and pharmaceuticals due to the textile industry and excessive usage of antibiotics have been detected in natural water sources. Hence, it is of high importance to remove or remediate such contaminants in water. TiO2 and ZnO nanoparticles are among the metal oxide semiconductor catalysts, which have been popularly used to remove a variety of contaminants in water. Unfortunately, these photocatalysts have various limitations such as wide bandgaps, rapid recombination rates, low surface areas, and their various synthetic routes use of hazardous reagents as reducing and stabilizing agents, which are a health hazard. In this study Commelina benghalensis (C. benghalensis) plant extracts were used to synthesize ZnO, TiO2, CuO-TiO2, 20/80 ZnO-CSs, (20/80) TiO2-CSs, CuO-TiO2-CSs, CuO-ZnO-CSs, 1 % Ag-ZnO-CSs. The novelty of the study focuses on the first time utilization of C. benghalensis plant extracts as greener and safer alternative way to synthesize all the photocatalysts that were environmentally friendly. To reduce the large bandgap of TiO2 and ZnO, these were coupled with CuO, to increase the surface areas these photocatalysts (TiO2, CuO-TiO2, ZnO and CuO-ZnO) were loaded on carbon materials and doping carbon-based photocatalysts with noble metals (Au and Ag) to help the recombination rate and increase the active sites, resulting in an enhanced photodegradation process. The sections (Chapter 4-8) explored the synthesis of ZnO, TiO2, CuO-TiO2, CSs, 20/80 ZnO-CSs, (20/80) TiO2-CSs, CuO-TiO2-CSs, CuO-ZnO-CSs, 1 % Ag-ZnO-CSs and 1 % Au-doped ZnO-CSs using various concentrations of C. benghalensis plant extracts. Various Characterization techniques such as FTIR, XRD, SEM, PL, TGA, BET, and UV-vis were used to characterise the photocatalysts. The FTIR revealed that tannins and flavonoid compounds from the plant were deposited on the photocatalysts; the peaks corresponding to the phytochemicals were more intense, when increasing the concentration of plant extracts. The presence of Zn-O and Ti-O-Ti vibrations were observed in the fingerprint region. More compounds such as alkaloids, esters, phenols, carboxylic acids etc. from the C. benghalensis plant extracts were confirmed by the LC-MS. The FTIR confirmed the presence of tannins and flavonoid, Cu-O and Ti-O-Ti peaks. An FTIR spectrum of microwave-synthesized carbon spheres showed the presence of carboxylic bond O–H, aliphatic groups asymmetric to the C–H, carbonyl stretch –C=O of carboxylic groups, the presence of C–C vibrations of aliphatic groups and the C-H vibrations. Therefore, the formation of carbon spheres was confirmed. Various photocatalysts were deposited on the CSs materials and the resulting FTIR spectra of various ZnO-CSs (5, 10 and 20 %) nanocomposites showed the presence of alkane molecules, hydroxyl, carboxylate, and carboxyl moieties. The metal-oxygen (Zn–O stretching vibrations), C–N bond stretching of the primary amine (which implies the presence of phytochemicals), asymmetric C–H, carboxylic groups, C=C stretching and C–C vibrations of aliphatic groups were also detected. The intensity of the ZnO peaks increased with the load percentage of ZnO on CSs. More peaks of the CSs were observed on the 5/95 ZnO-CSs than 10/90 and 20/80 ZnO- CSs nanocomposites. The formation of ZnO-CSs was confirmed by this spectrum. The 20/80 TiO2-CSs FTIR spectrum depicted the presence of Ti–O–Ti, Ti–O, and O– Ti–O bonds,–C–C–, H–O–H bonds and the C=O stretching of the carboxylic acid. The peaks at 1847-2158 cm-1 were attributed to the aliphatic –C–H, O-H. There was successful deposition of TiO2-NPs on CSs. For the CuO-TiO2-CSs, FTIR spectra showed Cu–O bond, O–H, Ti–O, Ti–O–Ti, C–H, –C=O and the C–C. These results confirmed the presence of CuO, TiO2 and CSs groups. The FTIR spectrum for the 20/80 CuO-ZnO-CSs reported the presence of the Zn–O, Cu–O bonds, C–H, C=C, O– H, –C=O and C–C groups. The functional groups clearly depicted that the sample contained CuO, TiO2 and CSs. However, as we were doping the ZnO and TiO2 photocatalysts with CuO, Au, Ag and loading the materials on CSs it is important to note that the intensity of peaks corresponding to the tannins and flavonoid compounds was decreasing. The XRD confirmed the formation of hexagonal wurtzite phase of ZnO and anatase phase TiO2 and a mixture of rutile and anatase phase. XRD confirmed the anatase phase of TiO2 and the tenorite phase of CuO. There was only one phase of TiO2 in the composite as compared to the pristine TiO2. The CSs XRD patterns noted the distinctive carbon peak at 21, 9°, which corresponds to the (002) plane was identified. The phase of the carbon spheres was amorphous, however the (100) plane of this material was not visible. The XRD pattern of ZnO-CSs (5, 10 and 20%) nanocomposites showed a broad peak at 21.6 associated to CSs, while the peaks associated ZnO are strongly suppressed by the incorporation of CSs. For the 20/80 TiO2-CSs XRD patterns intense diffraction peaks were visible in all TiO2, while crystalline TiO2 significantly suppressed CSs peaks. This is closely related to the charge recombination rate, making it favourable for photocatalytic activity. No additional impurity-related peaks were discovered. This indicated that the TiO2-NPs formed a clear anatase phase. The XRD data did not correlate with the FTIR data as various C-C groups were confirmed in the presence of CSs in the sample. The 2θ diffraction peaks for 20/80 CuO-TiO2-CSs corresponded to the CuO tenorite structure and the anatase phase of TiO2. This makes sense given that the lattice constants of anatase TiO2 are identical to those of CuO (tenorite). The intensity of TiO2 peaks is greater than that of CuO, indicating that TiO2 contributes more to the composite. All characteristic peaks related to TiO2, CuO, and no characteristic peaks associated impurities were observed. It was also discovered that the CuO-TiO2 phases did not change during composite formation and remained in anatase phase, and that its crystalline structure remained constant after aniline polymerization.The crystallinity 20/80 CuO-ZnO-CSs was investigated using XRD crystallography, CuO-NPs on CuO- ZnO compositions of varying percentages showed various peaks at 2θ angles that were assigned to tenorite CuO-NPs and the polycrystalline wurtzite ZnO-NPs. No visible peaks were detected for all the CSs sample, which means the sample is highly crystalline while the prepared was highly amorphous. It can be deduced that the CSs peaks were too small to even be identified since the presence of the CSs in the sample was detected by the FTIR spectra. The XRD patterns 1 % Ag-ZnO-CSs and 1% Au-ZnO-CSs diffractogram showed distinct peaks correspond to carbon sphere planes, hexagonal wurtzite structure, metallic silver and gold. The peaks corresponding to the ZnO-NPs were very small this may be due to the quantity of ZnO in the entire sample as only 20 % of ZnO-NPs was added. The UV-Vis displayed a maximum absorption band between 300 nm, 301, 5 nm, 280- 350 nm and 290-300 nm for CuO-ZnO, CuO-TiO2,10-30g ZnO and TiO2-NPs, respectively. v The UV-Vis absorption band for the CSs materials shows a broad peak around 300 nm and a shoulder around ~280 nm. These peaks can be attributed to →* transitions of aromatic C–C bonds and → * transitions of C=O bonds, respectively. All the ZnO-CSs exhibit a broad absorption peak at 300.7 nm and a shoulder peak around 287.5 nm. The absorbance band at 300.7 nm decreased with the increasing load percentage of ZnO on the CSs. While the shoulder peak around 287.5 nm was increasing in visibility with the increasing load of ZnO on CSs materials. There was no visible shift of the CSs peaks on the composite samples. The nanocomposites obtained in this study exhibited a slight move towards the infrared region as compared to the bulk ZnO, this is due to CSs chemical interaction with ZnO-NPs. UV-Vis absorbance spectroscopy of the (20/80) TiO2-CSs nanocomposites showed only one maximum absorbance sharp peak was visible at 285.7 nm. The addition of the TiO2 on the CSs material shifted the absorbance band to the lower UV region. The results indicate that the nanocomposites were more active in the UV region than the visible region of the spectrum. There were two broad peaks that were present in the 20/80 CuO-TiO2-CSs samples, the peaks were around 300.6 and 286.8 nm. The CuO- TiO2 nanocomposite exhibited a shift towards the UV region of the UV-vis absorption spectra, therefore the carbonaceous species in the as-synthesized 20/80 CuO-TiO2- CSs did not shift the material to the visible region. It is important to note that the carbon spheres synthesized in these studies were calcined via various temperature, while the CSs synthesized in the study was not calcined. The UV-Vis spectra for CuO-ZnO-CSs shows two peaks around 286.7 and 300.6 nm. Therefore, these materials were not active in the visible region of the spectrum. The UV-vis spectrum did no show improved optical properties on the CSs materials. The doped 1% Ag-ZnO-CSs and 1% Au-ZnO-CSs UV-Vis spectrum 301 nm and 287 nm, corresponding to ZnO and CSs, respectively. The 1% Ag-ZnO-CSs showed absorption bands at 298 nm and 286 nm, which are the absorption peaks Ag, ZnO- CSs, respectively.The presence of Ag caused a blue-shift in the absorbance spectrum as the maximum absorbance peak for Ag-ZnO-CSs is at 298 nm instead of ~301 nm, which was reported in chapter 7. The surface plasmon band of 1 % Ag-ZnO-CSs composite was noticeably broadened due to the strong interfacial electronic coupling between neighbouring ZnO and Ag nanoparticles. This plasmon oscillation may have vi caused a stronger light scattering influenced by the interaction of incident light and Ag nanoparticles, which helps to lengthen the optical path and reduces light energy loss even further. A band around 290 nm was recorded for the 1% Au-ZnO-CSs, which shows the presence of the Au in the ZnO-CSs material. The shift in ZnO band position in 1% Au- ZnO-CSs nanoparticles can be attributed to gold's higher electronegativity than silver. As a result, gold draws more electron density towards itself, affecting the movement of the band position of ZnO. The addition of photocatalysts and noble metals influenced the CSs material to be more active in the UV then the visible region of the spectrum. The bandgaps between 3.0-3.75 eV and 3.69-3.80 eV were obtained in ZnO and TiO2- NPs, respectively. Only the 10 g and 30 g ZnO reported reduced band gaps of 3.0 and 3.19 eV, respectively. The bandgap of CSs was reported to be 3.8 eV. The calculated the bandgap values were 3.8 eV, 3.5 eV and 3.78 eV 5/95 ZnO-CSs, 10/90 ZnO-CSs and 20/80 ZnO-CSs respectively. The bandgaps for the CuO, CuO-ZnO, CuO-TiO2 30/70, CuO-TiO2 50/50 and CuO-TiO2 70-30 were found to be 3.7 eV, 3.49 eV, 3.76, 3.72 eV and 3.79 eV, respectively. The obtained bandgaps are larger than 3.2 eV bandgap for the bulk ZnO, but smaller than the bandgap of CSs (3.8 eV). On the other hand, the bandgaps for 20/80 TiO2-CSs, CuO-TiO2-CSs and CuO-ZnO-CSs were 4.1 eV, 3.56 and 3.19 eV. Only the 20/80 CuO-ZnO-CSs reported the smallest bandgap of 3.19 eV. The corresponding bandgap of 3.75 eV for the 1% Ag-ZnO-CSs was calculated by extrapolating the linear region of the Tauc’s plot. This is because the nanocomposites synthesized in this study were active in the UV region rather than visible region. The bandgap of the 1% Au-ZnO-CSs was found to be 3.79 eV,. The presence of the Au NPs must have played a major role in the optical properties of the materials as these materials shifted to the lower UV region. The improvements on optical properties of these materials were insignificant. The Image J displayed particle size distributions of 60-80, 2-28 and 8-12 nm, for 10- 30 g ZnO-NPs and 100-300, 75-125 and 50-2 nm for 10-30 TiO2-NPs from the obtained SEM images of the photocatalysts. In chapter 4 and 5, SEM Images for both TiO2 and ZnO reported bigger particle sizes for lower concentration of the plant, since vii only fewer capping and reducing agents were present. Spherically-shaped materials were observed. The Image J reported particle size distributions of 50 nm–250 nm 100- 200 nm, 125-250 and 105-250, for CuO, CuO-TiO2 30-70, 50-50 and 70-30 was respectively. The larger particle sizes may be due to the agglomeration that was observed from CuO-TiO2 30-70 to 70-30. TEM images showed that the CSs were highly agglomerated, irregularly sized nanospheres, with sizes between ~10 nm to 100 nm. The TEM micrograms of CSs with various loadings of ZnO-NPs had mixed spherical and rod-shaped particles with a broad length distribution of 25-200 nm. As a result, when comparing the two nanoparticles, the CSs had larger particles than ZnO- NPs. TEM micrographs of the obtained 20/80 TiO2-CSs, CuO-TiO2-CSs and CuO- ZnO-CSs and the corresponding particle size distributions showed sherically and rod- likeshaped materials with particle size distributions of 25-200 nm, 100-600 nm and 50- 250 nm for 20/80 TiO2-CSs, CuO-TiO2-CSs and CuO-ZnO-CSs, respectively. The obtained 1 % Ag-ZnO-CSs and 1 % Au-ZnO-CSs nanomaterials TEM images showed spherically-shaped particles with length distributions ranging from 20 to 100 nm and 50 to 400 nm, respectively. The particles sizes of the noble metal-doped nanocomposites were smaller 20/80 ZnO-CSs with particle size distributions. The smaller sizes of materials favours high photocatalytic efficiency against dyes and pharmaceuticals. The BET surface areas were reported to be were 11.0723 m2/g, 8.8172 m2/g, and 7.1229 m2/g for 10 g, 20 g and 30 g ZnO-NPs, respectively. For the 10 g, 20 g, and 30 g TiO2-NPs, the BET specific surfaces were 18.3 ± 0.173 m2 /g, 12.3 ± 0.146 m2 /g, and 174.6 ± 1.35 m2 /g, respectively. The surface areas decreased with an increased concentration of plant extract for ZnO-NPs and TiO2-NPs (10-20 g), while for TiO2- NPs the 30 g TiO2-NPs had a BET surface area of 174.6 m2 /g. The BET surface areas were 5.58, 5.74 and 3.22 m2 /g for CuO-TiO2 30-70, 50-50 and 70-30,respectively. The 20/80 ZnO-CSs nanocomposite had a surface area of 21.95 m2 /g (Figure 7.10b). The isotherm (demonstrated a hysteresis loop of type H2, indicated a mixture of macropores and mesopores while the BET surface area curves for the 20/80 TiO2- CSs, CuO-TiO2-CSs and CuO-ZnO-CSs can be classified as a typical type IV isotherm, which belongs to a hysteresis loop type II indicating a purely mesoporous material with small pore sizes. The BET surface area was 1.676 m2 /g, 2.890 m2 /g viii and 40.740 m2 /g for 20/80 TiO2-CSs, CuO-TiO2-CSs and CuO-ZnO-CSs, respectively. The thermal stability of both ZnO and TiO2-NPs decreased with increasing concentration of plant extract. The final weight % at 900 0C for 10-30 g were 98.9, 93.2 and 84.6 % for ZnO-NPs and 97.9, 96.4 and 96.4 % for TiO2-NPs ,therefore, these materials were highly stable under extremely high temperatures therefore suitable for photocatalysis. Three CuO-TiO2 materials were thermally stable as only a maximum of ~8 % weight loss was noted for the 70/30 CuO-TiO2 at 900 0C. Nanocomposites were slightly less stable than green synthesized TiO2 as the maximum weight loss of ~4 % was reported. The TGA analysis of CSs reported a total mass loss of CSs was about 50 % at 900 0C. These CSs were thermally unstable at higher temperature this means the addition of our photocatalysts on the CSs will increase their stability. TGA curves of 20/80 ZnO-CSs (Figure 7.9a) show a slow rate of weight loss of 10 % up to 100 0C, indicating that volatile substances and water in the samples evaporate [390]. The second stage of weight loss occurred between 105 and 200 0C (3.7 % weight loss) due to the dehydration of water within the ZnO structure [423], and the final stage between 200 and 900 0C (46.1 % weight loss) to the decomposition of ZnO- CSs. The thermal stability and the derivative of (20/80) TiO2-CSs, CuO-TiO2-CSs, CuO-ZnO-CSs and ZnO-CSs showed that only 44.7 % of weight was lost at 900 0C. The TGA revealed about 49.9% weight loss at 900 0C for the CuO-TiO2-CSs and the TGA of 20/80 CuO-ZnO-CSs nanocomposites showed the most stability than the (20/80) TiO2-CSs and CuO-TiO2-CSs nanocomposites as about 43.1% weight was lost at 900 0C compared to the 44.7 % and 49.9 % of (20/80) TiO2-CSs and CuO-TiO2- CSs, respectively. Adding the photocatalysts to the CSs improved their thermal stability. 1 % Ag-ZnO-CSs and 1 % Au-ZnO-CSs structures and the final stage between 400 and 900 0C a total weight loss of 64.3 % and 69.6 % was reported, respectively. These results show that the 1 % Ag-ZnO-CSs is more thermally stable than the 1 % Au-ZnO- CSs. And that both materials are less stable than the 20/80 ZnO-CSs, as the total weight percentage at 900 0C was approximately 54.2 %, 36.4 % and 29.7 % for 20/80 ZnO-CSs, 1 % Ag-ZnO-CSs and 1 % Au-ZnO-CSs, respectively. 74.2 % at 700 0C for the Ag-doped ZnO-C material. ix The highest degradation of 81 % for methylene blue (MB) was reported by 30 g ZnO- NPs while the 30 g TiO2-NPs reported 65 % degradation of MB. The degradation of sulfisoxazole (SSX) was 42 % and 82 % for 30 g ZnO and 30 g TiO2-NPs, respectively. Both ZnO and TiO2-NPs were only reusable once and the •OH were the species responsible in the degradation of MB. Degradation of MB was 14, 33 and 12 % for 30/70, 50/50 and 70/30 CuO-TiO2. The degradations of SSX and ciprofloxacin (CIP) were 93.6, 93.2 and 91.2 %, respectively. While for the 30/70, 50/50 and 70/30 CuO- TiO2, the degradations were 5.06, 55.3 and 67.3 %, respectively. On the photodegradation analysis various photocatalysts of CSs, 20/80 TiO2-CSs, CuO-TiO2-CSs, CuO-ZnO-CSs and 20/80 ZnO-CSs were tested for their efficiency against MB dye using similar MB conditions that was reported in Chapter 4-6. The highest degradation of CSs, TiO2-CSs, CuO-TiO2-CSs, CuO-ZnO-CSs and (5 %, 10 % and 20 %) ZnO-CSs was ~25, 36, 41, 40, 36 and 42 %, respectively. From these values it can be noted that the addition of photocatalysts on the CSs improved only the degradation efficiency of the CuO-TiO2 (Chapter 6) nanocomposites against MB. Since the highest degradation efficiency of CuO-TiO2 nanocomposites was reported to be 33 %. While the addition of CSs regressed the degradation of ZnO and TiO2 against MB as the highest degradation was reported to be 81 and 65 %, respectively (Chapter 4 and 5) The majority of materials achieved the first order of kinetics because the R2 is closer to 1. The reaction rate for CSs was 0.0025 min-1 . While the reaction rates for 5/95 ZnO-CSs, 10/90 ZnO-CSs and 20/80 ZnO-CSs were 0.004, 0.003, and 0.003 min-1 , respectively. The reaction rates of 0.0023, 0.0028, and 0.002 min-1 were reported for the (20/80) TiO2-CSs, CuO-TiO2-CSs and CuO-ZnO-CSs respectively. The highest degradation rates of 75 %, 92 % and 98 % for the 20/80 ZnO-CSs, 1 % Ag-ZnO-CSs and 1 % Au-ZnO-CSs, respectively were found. The synthesized 20/80 ZnO-CSs, 1 %Ag-ZnO-CSs and 1 % Au-ZnO-CSs nanocomposite did not achieve the first order of kinetics because the R2 was not closer to 1. The reaction rates of 20/80 ZnO-CSs, 1% Ag-ZnO-CSs and 1 % Au-ZnO-CSs were 0.00368, 001017 and 0.00196, respectively. The 20/80 ZnO-CSs, at optimum conditions ( pH5, 45 mg dosage, 5 mg/L dye) showed a slight improvement and had the highest degradation of 75%. x Studies reported that the ZnO-CSs exhibited improved photocatalytic activity under sunlight and visible light irradiation after the addition of CSs, which is attributed to the CSs' extended light absorption range and fast separation of photogenerated charge carriers. The findings of this study are almost comparable to those of other studies published in the literature where UV, visible and sunlight light sources were used to degrade organic materials using similar nanocomposites. During photocatalysis, trapping studies were carried out to assist understand the reaction mechanism and identify the reactive species involved. Chemical species such as tert-butanol, EDTA, AgNO3, and p-benzoquinone (BQ) were used as •OH radicals, holes (h+ ), electrons (e- ) and superoxide ion (O2 2- ) trappers and scavengers in the reaction system, respectively. For the ZnO-NPs only the 30 g of ZnO-NPs was used against the MB for all the trapping studies. It was noted that the addition of the EDTA decreased the degradation by 30% which meant that the presence of the electrons (e- ) played a minor role in the photodegradation of MB. In opposition, the addition of t-BuOH and AgNO3 decreased the photocatalytic degradation of MB by 49 % and 54 %, respectively. The addition of t-BuOH affected the degradation of MB, the most compared to the AgNO3 and EDTA, indicating that the •OH.radicals were the main active species. Similar procedure was followed for the TiO2-NPs as the degradation of MB with 30 g TiO2-NPs was used for all trapping studies. The addition of EDTA and AgNO3 increased the degradation by 17 and 3 %, correspondingly, implying that the presence of both electrons (e- ) and holes (h+ ) did not play a role in degrading the MB dye comparing to the other species. The addition of t-BuOH resulted in 34% reduction in the degradation and had the greatest effect, thus implying the •OH radicals were the dominant species. In chapter 6, the active species for SSX antibiotic degradation were associated with e- and •OH. The p-n heterostructures influenced both the e- and the •OH radical to be active species in the degradation of SSX antibiotic. This may have played a major role in the degradation of both MB and SSX. The degradation of MB decreased drastically as compared to the degradation of MB using green synthesized TiO2 where only the •OH radicals were the major active species in the degradation process. On the other xi hand, the presence of these two active species improved the degradation of SSX as the maximum of 94 % was degraded as compared to the degradation of 82 % reported for the TiO2-NPs. The reusability of a material is an important factor to consider when dealing with the cost and an efficiency of a material. The reusability studies were carried out using 30 mg of 30 g C. benghalensis ZnO-NPs photocatalyst, using a 20 ppm MB concentration and the catalyst was reused for three cycles. The 30 g C. benghalensis ZnO-NPs residue was washed with distilled water several times. The recovered 30 g C. benghalensis ZnO-NPs was then used without further treatment in a new photodegradation batch. It can be noted that after each reuse, the efficiency was reduced till 37% in cycle 4. The inefficiency after the material was reused could have been due to poisoning, loss of catalyst, catalyst coverage etc. as these have been noted in other studies. The reusability tests were performed with the C. benghalensis TiO2-NPs (30 g) photocatalyst since the material gave the highest degradation of 65% against MB. From the UV-vis curves obtained, it showed that the degradation of MB with the 30 g TiO2-NPs decreased after each cycle which was a similar behaviour that was observed with the 30 g ZnO-NPs. The photocatalytic effectiveness of the catalyst decreased by 29% after four cycles. The TiO2 material could not maintain its effectiveness even after the first cycle. When reusability studies were conducted on the SSX antibiotic, using the 30/70 CuO- TiO2 nanocomposite, the photocatalyst was both stable and reusable in four cycles. The formation of the CuO-TiO2 heterojunction was a major improvement on the TiO2 photocatalyst, as the material was reusable only once. The reusability studies for four cycles using the 1 % Au-ZnO-CSs are shown in with a 2 h UV light exposure duration, for each cycle. The catalyst was not stable as the degradation was reduced from the 1st cycle by more than 50%. After the 4th cycle, a complete collapse in the degradation took place. To test the efficiency of the 1% Au- ZnO/C against other pollutants, this material was tested against various pharmaceutical pollutants. The degradation of pharmaceuticals (CBZ, CIP, SMX and SSX), were conducted by using 100 mg photocatalyst and 10 mg/L concentration of contaminant. Similar xii conditions as with MB were followed for the 1 % Au-ZnO-CSs photocatalyst, which degraded about 96 % (SSX), 89 % (CIP) 78 % (SMX) and 29% (CBZ). This means that the 1 % Au-ZnO-CSs is the best photocatalyst, which can degrade various contaminants. The incorporation of ZnO-NPs carbon spheres and the addition of noble metals have indeed improved the degradation efficiency of the material as the degradation of MB by ZnO-NPs as reported in Chapter 4 was 81 % by incorporating the material on 80% CSs (under optimised conditions) the degradation decreased to 75 % and lastly doping the 20/80 ZnO-CSs with 1 % Ag and 1 % Au further increased the degradation of MB to be 90 % and 98 %, respectively Such a degradation was associated with a higher surface defect, i.e., VO observed for 20/80 ZnO-CS. This material was doped with 1 % Ag and Au separately. This study demonstrated that environmentally friendly materials can be created and used to degrade dyes and antibiotics. The deposition of nanocomposites from Chapter 4-7 on carbon spheres and doping carbon-based materials with noble metals (ag and Au) improved the material’s efficiency. The study proved that green-synthesized heterostructures were effective against various contaminants and C. benghalensis plant is a safer and greener reducing and capping agent.
Thesis (Ph.D. (Chemistry)) -- University of Limpopo, 2023
Keywords: Organic dyes; Textile wastewater; Green synthesized metal oxide; Carbon-based nanomaterials; Sewage; Nanostructured materials; Dyes and dyeing -- Chemistry; Water reuse; Water -- Pollution